PATCH EKSTRAK DAUN SIRIH (Piper betle L.): EVALUASI AKTIVITAS ANTIBAKTERI, PROFIL PELEPASAN EUGENOL dan TOLERANSI LOKAL - Mufrod Mufrod; Suwaldi Suwaldi; Subagus Wahyuono (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Piper betle leaf in extract form is more effective than crude drug. Eugenol is a component in the extract that has antibacterial activity but irritate. Patch of piper betle leaf extract was used on the mucosa to make oral cavity hygiene. Antibacterial activity was influenced by the release of eugenol from the patch. Release enhancer substances (RES) such as glycerin, propylen glicol and tween 80 were added in patch formulation to increase the release of active substances. The aim of the research was to investigate the physicochemical properties, eugenol release profiles, and local tolerance test of the patch. Extract of piper betle leaf was made using infundation method. Patch was made according to the variation concentration of extract (1, 2 and 4%) and RES (glycerine, propylen glycol and tween 80) using chitosan as vehicle. Patch produced solvent casting method. Patch obtained was tested for swelling index, folding endurance, surface pH, antibacterial activity, release of eugenol, and local tolerance. Data obtained were analyzed descriptively. The result showed that the addition of RES did not affect the surface pH but increase the water absorption with in inconsistent way except patch with tween 80. The flexibility (folding endurance value) increased, and the highest amount of eugenol released was achieved by patch using propylen glicol. Patch with tween 80 and glycerin for all extract concentration and patch with 1% extract concentration using propylen glycol showed medium sensation (local tolerance), and patch with 2 and 4% extract using propylen glycol showed severe sensation.